Evaluación del manejo integrado del cultivar grand nain, rendimiento y fitosanidad. - Manrique Toro, Paco Anival (Machala : Universidad Técnica de Machala, 2022)
In the Ecuadorian agricultural production sector, the agricultural activity of greatest economic importance is the cultivation of bananas, representing 3.84% of the total GDP, 50% agriculture, and 20% of the country's exports. Banana grows in the provinces of Manabí, Los Ríos, Guayas, El Oro and Esmeraldas. Within the province of El Oro, the main cantons where bananas are grown are: Machala, Pasaje, Santa Rosa, Arenillas and El Guabo. The Ministry of Agriculture, Livestock, Aquaculture and Fisheries registered that, of the 162,039 hectares of existing farms, 12% represents organic bananas and 88% is conventional. In 2015, about 50% of Ecuadorian banana exports went to Russia, the United States and Germany, around 20.22%, 15.39% and 11.97% respectively. Among other places with low participation, Turkey has around 7.67%, China 4.62%, Belgium 4.50% and Argentina 4.13%. The objective of this work was to evaluate the effect of edaphic fertilization, plus the application in drench of efficient microorganisms in the integrated management of banana cultivation. The present research essay was carried out in the banana plots, located in the Santa Inés Experimental Farm, belonging to the Technical University of Machala, in the Faculty of Agricultural Sciences. In the experimental area, a randomized block design with 4 treatments and 15 repetitions was used: T1 = Urea 30 g + FossilShell 5 g + SULPOMAG 30 g + 1 liter of ME (efficient microorganisms) (1000 cc); T2= Urea 30 g + FossilShell 5 g + Agacomplex 100 g + SULPOMAG 30 g; T3 = Potassium Nitrate 30 g + FossilShell 5 g + Agacomplex 100 g + SULPOMAG 30 g; T4 = Ammonium nitrate 30 g + FossilShell 5 g + Agacomplex 100 g + SULPOMAG 30 g + 1 liter of ME (1000 cc). The variables studied were: (EF) Foliar Emission; (ALT) Plant height; (LHOJA) Leaf Length; (AHOJA) Sheet Width; (PR) Bunch Weight; (PRQ) Rachis weight; (ASON) Height of the Son; (MDS) Measurement or gauge of the hand of the sun; (ULM) Measurement or caliber of the last hand of the bunch; (PMS) Weight of the sun's hand; (PULM) Weight of the last hand of the bunch; (NDMS) Number of fingers on the sun's hand; (NDULM) Number of fingers of the last hand of the bunch; (NM) Number of hands in the bunch; (DP) Days to calving; (DC) Days to harvest. The effect of mineral fertilization and efficient microorganisms in the integrated management of banana cultivation was evaluated through the monthly application of fertilizers in recommended doses, showing that not all treatments presented significant differences within the variables studied, only significant differences between the variables EF, PR, PMS, PULM. Regarding the sowing of the Gran Nain banana cultivar, in order to evaluate its productivity with various treatments, it was identified that it has a good yield compared to other cultivars within the area and these vary depending on the agronomic management. of the crop. Banana cultivation was monitored with its agronomic management in order to identify the responses with various chemical treatments and efficient microorganisms, between the treatments studied there were no relevant significant differences, however treatment 1 and treatment 4 presented numerical differences, both with the presence of beneficial microorganisms, which should be considered for future studies.
En el sector productor agrícola ecuatoriano, la actividad agrícola de mayor importancia económica es el cultivo de banano, representando el 3,84% del PIB total, el 50% agrícola, y el 20% de las exportaciones del país. El banano crece en las provincias de Manabí, Los Ríos, Guayas, El Oro y Esmeraldas. Dentro de la provincia de El Oro, los principales cantones donde se cultiva banano son: Machala, Pasaje, Santa Rosa, Arenillas y El Guabo. El Ministerio de Agricultura, Ganadería, Acuacultura y Pesca registró que, de las 162.039 hectáreas de fincas existentes, el 12% representa a banano orgánico y el 88% es convencional. En 2015, cerca del 50% de las exportaciones de banano ecuatoriano se envió a Rusia, Estados Unidos y Alemania, alrededor del 20,22%, 15,39% y 11,97% respectivamente. Entre otros lugares con baja participación, Turquía tiene alrededor del 7,67%, China el 4,62%, Bélgica el 4,50% y Argentina el 4,13%. El presente trabajo tuvo como objetivo evaluar el efecto de la fertilización edáfica, más la aplicación en drench de microorganismos eficientes en el manejo integrado del cultivo de banano. El presente ensayo de investigación se realizó en las parcelas de banano, ubicada en la Granja experimental Santa Inés, perteneciente a la Universidad Técnica de Machala, en la Facultad de Ciencias Agropecuarias. En el área experimental se empleó un diseño de bloques al azar con 4 tratamientos y 15 repeticiones: T1 = Urea 30 g + FossilShell 5 g + SULPOMAG 30 g + 1 litro de ME (microorganismos eficientes) (1000 cc); T2= Urea 30 g + FossilShell 5 g + Agacomplex 100g + SULPOMAG 30 g; T3 = Nitrato de Potasio 30 g + FossilShell 5 g + Agacomplex 100g + SULPOMAG 30 g; T4 = Nitrato de amonio 30 g + FossilShell 5 g + Agacomplex 100g + SULPOMAG 30 g + 1 litro de ME (1000 cc). Las variables estudiadas fueron: (EF) Emisión Foliar; (ALT) Altura de planta; (LHOJA) Largo de Hoja; (AHOJA) Ancho de Hoja; (PR) Peso del Racimo; (PRQ) Peso del Raquis; (AHIJO) Altura del Hijo; (MDS) Medición o calibre de la mano del sol; (ULM) Medición o calibre de la Última mano del racimo; (PMS) Peso de la mano del sol; (PULM) Peso de la última mano del racimo; (NDMS) Número de dedos de la mano del sol; (NDULM) Número de dedos de la última mano del racimo; (NM) Número de manos del racimo; (DP) Días a la parición; (DC) Días a la cosecha. Se evaluó el efecto de la fertilización mineral y los microorganismos eficientes en el manejo integrado del cultivo de banano, mediante la aplicación mensual de los fertilizantes en dosis recomendados, evidenciando que no todos los tratamientos presentaron diferencias significativas dentro de las variables estudiadas, sólo se presentaron diferencias significativas entre las variables EF, PR, PMS, PULM. En cuanto a la siembra del cultivar de banano Gran Nain, con el fin de evaluar su productividad con diversos tratamientos se identificó que tiene un buen rendimiento en comparación a otros cultivares dentro de la zona y estos varían en función del manejo agronómico del cultivo. Se monitoreó el cultivo de banano con su manejo agronómico con el fin de identificar las respuestas con diversos tratamientos químicos y microrganismos eficientes, entre los tratamientos estudiados no existieron diferencias significativas relevantes sin embargo el tratamiento 1 y tratamiento 4 presentaron diferencias numéricas, ambos con presencia de microorganismos benéficos, que deben ser consideras para futuros estudios.
Keywords: BANANO; IMPULSAR; TRATAMIENTOS; FERTILIZANTES MINERALES; DRENCH